Bantuan Alat Dan Pengenalan Printer 3d Tipe Fff/Fdm Untuk Santri Pondok Pesantren Darul Muttaqin Kota Batu (Fakultas Teknik, Universitas Brawijaya, 2025)
Darul Muttaqin Islamic Boarding School in Batu City as an Islamic boarding school that focuses on religious education faces challenges in introducing modern technology that is currently trending to its students, especially in the manufacturing sector. One of the solutions we offer is to provide tools and training in the use of FFF/FDM type 3D Printers. In order to improve technological skills and knowledge, this program aims to introduce and implement 3D printing technology into the Islamic boarding school education curriculum, as well as provide opportunities for students to develop creativity and innovation in making prototypes and products based on 3D printing technology. Through this activity, we hope to improve the understanding and utilization of modern technology among students of Darul Muttaqin Islamic Boarding School.